Mapping Bodies - MINKLEY, EMMA (Kronos: Southern African Histories, 2020)
The images in the visual essay that follows this text are drawn from a set of partnered art events, the Museum of Truth and Reconciliation and Double Portrait/Haunting Objects. The latter took place at the University of the Western Cape in Cape Town, South Africa, in March 2018 as part of the programme at the workshop titled, ‘Missing and Missed: The Subject, Politics and Memorialisation’, and was intended to be read as a second chapter of the Museum of Truth and Reconciliation, which was enacted in Toronto, Canada in October 2016. The Toronto event invited participants to compile and collate objects collected from the streets of the city in response to a suite of cue cards containing pictorial and textual prompts on themes relating to truth and reconciliation, loss and memory.1 The collected objects, ranging from bits of organic matter to written pamphlets to foodstuffs, are now stored in small compartmentalised plastic ‘collector’s boxes’ – each imbued with individualised notions of the given prompts. The cue cards exist as a set of indexical maps. Simultaneously images and objects, they hold information on routes through the city, as well as outlines of things and ideas, lost and found.